Evaluating the employability skills of industrial engineering graduates: A case study - MacKieh, Adham Ahmad; Dlhin, Faeza Saleh A. (Tempus Publications ijee@eircom.net, 2019)
Incorporation of employability skills in the industrial engineering curriculum to bridge the gap between industry and institutions of higher education has become a major issue. This study appraises the employability skills of industrial engineering graduates based on the skills that required additional training, skills that are needed for job performance and skills that are received/emphasized in the curriculum.Twobatches of questionnaires are administered to the participants of the study. The first batch is administered online to students, employed alumni and faculty members. The second batch is distributed to instructors of core courses. Thirty-six items of skills are arranged under seven basic employability skills that were previously reported are employed in the evaluation. Of the seven employability skills, following management, leadership and information technology skills are identified as skills that require additional training. The responses toward skills required for job performance and skills that are received/emphasized in the curriculum are ranked higher by participants based on the percentage of agreement. This study advocated that the perception of participants provides greater insight into the skills items that should be emphasized in the industrial engineering curriculum to enhance the employability of graduates. © 2019 TEMPUS Publications.
Keywords: Attitudes; Curriculum; Employability skills; Performance skills; Training